Risk Factors and Severity of Coronary Lesions in Acute Coronary Syndrome - Manalu, Karina Yesika; Masyhudi, Alysa Masytha; Galenta, Yusuf; Sitompul, Sanggap Indra (Transpublika Publisher, 2026)
Acute coronary syndrome (ACS) is associated with significant morbidity and mortality in Indonesia, with multivessel disease (MVD) linked to worse outcomes, yet individual risk factors’ roles in lesion severity remain unclear in rural settings. This study is done to identify risk factors influencing coronary lesion severity (SVD vs. MVD) in ACS patients. This cross-sectional study at Dr. Doris Sylvanus General Hospital (July 2023-October 2024) included 85 ACS patients undergoing angiography/PCI, categorized by SVD (n=26, 30.6%) or MVD (n=59, 69.4%). Clinical data were extracted from emergency department records, including demographic characteristics (age, sex), medical history (hypertension, diabetes mellitus, dyslipidemia), smoking status, as well as physical examination and laboratory findings such as blood pressure, body mass index (BMI), and Free Blood Sugar levels, which were used to support the classification of corresponding risk factors. SPSS v29 facilitated bivariate/multivariate logistic regression (p<0.05). The findings of this study show that no individual risk factor significantly predicted MVD (all p>0.05; diabetes OR=2.059, p=0.409). However, ≥3 cumulative risk factors strongly associated with MVD (3 factors: 80%, p=0.022; 4-9 factors: 65.5%, p=0.038). A higher burden of cumulative risk factors, not isolated ones, is associated with MVD in this rural ACS cohort, suggesting the potential value of integrated screening for early risk stratification.